The Mediating Role of Organizational Culture in the Relationship Between Management Financial Information and Organizational Performance in Kurdistan Manufacturing Companies - Yousif Mohammed Babakr HajiEbrahim; Barzan Mohammed Qader; Sardar Jalal Braim (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
This study aims to explore the intricate interplay between organizational culture, management financial information systems and organizational performance within Kurdistan manufacturing companies. Despite the well-established importance of financial information in decision-making and performance evaluation, limited attention has been given to how organizational culture mediates this relationship, especially in the unique context of Kurdistan. As a result, a structural equation model was estimated using 186 responses collected from a randomly selected cluster of manufacturing companies in Erbil, Kurdistan. According to the results, the significantly positive interplay between management financial information systems (MFIS) and organizational culture suggests that MFIS not only transform organizational processes but also foster a culture that is conducive to continuous improvement and strategic success. The study showed that the anticipated benefits of MFIS might not be realized uniformly across organizations, possibly due to variations in the existing organizational frameworks, cultural readiness, or the level of system integration. Apart from proving that organizational culture significantly mediates MFIS’ impact on organizational performance, our findings reinforce the established understanding that organizational culture is a pivotal factor in determining organizational performance. When implementing MFIS, organizations should adopt a holistic approach that integrates cultural change management with technological deployment.